Artificial intelligence : methodology, systems, and applications : 18th International Conference, AIMSA 2018, Varna, Bulgaria, September 12-14, 2018, Proceedings /: methodology, systems, and applications : 18th International Conference, AIMSA 2018, Varna, Bulgaria, September 12-14, 2018, Proceedings. (2018) - Unknown
No abstract available